Peningkatan Kreativitas Anak melalui Permainan Papier-Mache di Pendidikan Anak Usia Dini - Retno Wulandari; Issaura Dwi Selvi (Jurnal Pelita PAUD, 2020)
This study, entitled Increasing Creativity Through Play Papier-Mache Activity In Children Group B in early childhood Sebiduk Sehaluan Dwi Asih Rawabening, which aims to promote creativity in children in group B. The data obtained by observation in each cycle. The subjects were children aged 5-6 years who numbered 13 children of the school year 2015-2016. From the analysis of data obtained by an increase of pre-cycle, the first cycle and the cycle 2, respectively are two children (15%) increased to 4 children 31% and increasing to 11 children (85%) who scored at least growing in line with expectations (BSH ). This can be seen in every cycle indicator that often arises is fluency is 87%, flexibility 85% dan originality is (100%), and an indicator which not often arises is elaboration which just a 31% and redefinition 31%. Keywords: Creativity, Game, Papier-mache.